Answers

  • Brainly User
2015-05-17T18:35:31+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
I hope u will satisfy with my ans 
0
2015-05-18T21:13:17+05:30
  cos(a-b) = cos(a)cos(b) + sin(a) sin(b) 
cos 11 = cos (56-45) = cos 56 cos 45 + sin 56 sin 45 = cos 56 / √2 + sin 56/√2 
sin(a-b) = sin(a) cos(b) - cos(a) sin(b) 
sin 11 = sin(56-45) = sin 56 cos 45 - cos 56 sin 45 = sin 56 /√2 - cos 56 / √2 

cos 11 + sin 11 = cos 56 / √2 + sin 56/√2 + sin 56 /√2 - cos 56 / √2 
cos 11 + sin 11 = (2/√2) sin 56 
cos 11 - sin 11 = cos 56 / √2 + sin 56/√2 - sin 56 /√2 + cos 56 / √2 
cos 11 - sin 11 = (2/√2) cos 56 

(cos 11 + sin 11)/(cos 11 - sin 11) = (2/√2) sin 56 / (2/√2) cos 56 
= tan 56
0